Gingival veneer used as prosthetic solution for esthetic-compromised malpositioned dental implant - Viviane Ankli; Francisco Ivison Rodrigues Limeira; Monica Yamauti; Tassiana Cançado Melo Sá (Wolters Kluwer Medknow Publications, 2018)
Implant therapy has become a common practice and esthetic demands have tremendously increased, especially in the replacement of anterior teeth in patients with a high lip line. This report presents a gingival veneer as a viable treatment modality to mask peri-implant marginal gingival defects. An impression of the upper arch was made and the gingival veneer was waxed, and clinical confirmation was obtained, followed by laboratory processing, finishing, and polishing. After installing, it adapted to the proximal niches and exhibited good stability. A gingival veneer can be a feasible alternative with excellent esthetic results, when indicated and correctly executed to mask possible defects in the peri-implant marginal gingiva associated with a malpositioned single dental implant.